A method for preparing lithium aluminum silicon glass-ceramics with high aluminum content without nucleating agent
Through the preparation method of high-aluminum content lithium-aluminum silicon microcrystalline glass without nucleating agent, the glass composition and heat treatment process are optimized, and the problem of light transmittance and cost increase caused by nucleating agent is solved, and high light transmittance and excellent mechanics are achieved Performance of microcrystalline glass.
Patent Information
- Application Number
- CN202410297955.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-03-15
AI Technical Summary
The existing lithium aluminum silicon crystal crystallized glass uses nucleating agents during the preparation process, resulting in a decrease in the light transmittance of the glass, an increase in coloring and preparation cost, and it is difficult to control the crystal size and composition, affecting the mechanical and optical properties of the material.
The preparation method of high-aluminum content lithium-aluminum silicon microcrystalline glass without nucleation agent is adopted. Through the optimization of the glass composition and two-step heat treatment process, transparent microcrystalline glass with high light transmittance and excellent mechanical properties are formed. The specific steps include preparing the precursor glass through melt cooling method, and preparing transparent microcrystalline glass through a two-step heat treatment method to adjust the grain size and physical properties.
High light transmittance and excellent mechanical properties are achieved, reducing the coloring and cost increase brought by nucleating agents, and improving the efficiency of microcrystalline glass in ion exchange surface strengthening.
Smart Images

Figure CN118184153B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microcrystalline glass, and specifically to a method for preparing lithium aluminum silicon microcrystalline glass with high aluminum content without a nucleating agent. Background Art
[0002] Transparent superhard materials are key materials for display cover plates of electronic devices, including smartphones. Although tempered glass is inferior to sapphire in terms of mechanical properties, scratch resistance, and drop resistance, it has extremely low manufacturing costs and energy consumption compared to sapphire, is lightweight, has high light transmittance, and can adapt to aesthetic designs such as curved edges. These factors will ensure that tempered glass will still occupy a large application market in the future.
[0003] Adding aluminum to silicate glass can improve mechanical properties, such as hardness and scratch resistance. High-aluminum silicate glass refers to a type of glass that has good mechanical and chemical properties due to the addition of a higher content of Al2O3 to the glass composition. High-aluminum silicate glass is a type of glass with high aluminum and high alkali content. Compared with other ordinary glasses, high-aluminum silicate glass has strong mechanical properties because Al can form aluminum-oxygen tetrahedral structural units to repair the glass network structure. It is currently widely used in touch screen cover glass. However, the defects remaining in the glass during the manufacturing process and the scratches accumulated during use make its mechanical strength significantly lower than its theoretical strength. Microcrystallization (forming microcrystalline glass) and chemical strengthening (ion exchange surface strengthening) are effective methods to improve the mechanical properties of glass cover materials.
[0004] Glass-ceramics is an inorganic composite material in which fine crystals are dispersed in an amorphous glass matrix by further heat-treating the precursor glass. It has superior mechanical properties to glass. Glass-ceramics prepared by heat-treating high-alumina-silica glass can significantly improve the thermal properties, chemical stability, and mechanical strength of the precursor glass without reducing the light transmission performance, and can provide a more impact-resistant, durable, and scratch-resistant glass-ceramics cover for touch display devices. The typical aluminosilicate glass-ceramics system, Li2O-Al2O3-SiO2 (lithium aluminum silicon), is the most commonly used glass-ceramics for manufacturing cookware plates, kiln facility viewing windows, telescopes, laser gyroscopes, and personal electronic device cover screens due to its ultra-low thermal expansion rate, satisfactory transparency, and excellent scratch resistance. Although the various properties of glass-ceramics are generally higher than those of ordinary glass, its transparency may be significantly reduced after the glass crystallizes, which greatly limits its scope of application. The main reason for the reduction in the transmittance of microcrystalline glass is the scattering of incident light at the grains in the microcrystalline glass and the difference in refractive index between the grains and the glass matrix. Therefore, in order to obtain highly transmittance microcrystalline glass materials, it is necessary to optimize the composition and crystallization heat treatment process conditions so that nano-scale grains with a composition and refractive index close to the main body of the glass matrix are precipitated in the glass matrix.
[0005] The composition of the precursor glass will significantly affect the formation and performance of glass-ceramics. The formation of glass-ceramics includes two processes: the formation of crystal nuclei and the growth of crystals. The crystallization heat treatment process conditions for preparing glass-ceramics also depend on the composition of the precursor glass. The size of the crystallites in the formed glass-ceramics and the interface state between the grains and the glass matrix significantly affect the physical properties of the glass-ceramics. At present, the Al2O3 content in most lithium-aluminum-silicon system glasses is not high and the composition contains one or more composite nucleating agents. The most widely used nucleating agents for preparing lithium-aluminum-silicon glass-ceramics are TiO2, ZrO2, P2O5, SnO2, Cr2O3, etc. Their common characteristics are high cationic charge and relatively large field strength, which have a strong accumulation effect on the structure of the glass and can accelerate the phase separation of the glass, thereby achieving the purpose of nucleation and crystallization.
[0006] However, although nucleating agents can promote glass crystallization, they also bring many negative effects besides increasing the additional preparation cost: (1) After adding nucleating agents, the crystallization speed of many glasses will be accelerated during the heat treatment process, and the crystallization temperature range is narrow. It is difficult to control the crystal size through heat treatment, and the optical properties of microcrystalline glass will deteriorate or even become devitrified. (2) The introduction of these nucleating agents may cause the glass to be colored. For example, Sn ions, Ti ions, Cr ions, and Fe ions will form low-valent ions during the crystallization heat treatment process or under the conditions of photoreduction by irradiation, thereby generating light absorption in the visible light region, reducing the transmittance of microcrystalline glass and generating dispersion. Mixed nucleating agents of ZnO and TiO2 will also make the glass white. (3) In addition, the refractive index of the precipitated crystals during the heat treatment process of preparing microcrystalline glass can only be adjusted within a small range, and the composition of the precipitated crystals is required to be as consistent as possible with the composition of the residual glass phase. However, the nucleating agent itself may also produce precipitated impurities such as ZrO2, ZrTiO4, phosphate, and titanate. Among them, ZrO2 has a low solubility in silicate system glass. If the mass percentage is more than 3%, it will cause difficulty in dissolving and precipitate from the melt. For this microcrystalline glass system with a non-single main crystal phase, it is obviously difficult to require the precipitated crystals to be as consistent as possible with the residual glass phase. The refractive index difference between the formed multiple crystalline impurity phases and the matrix glass is relatively large, which affects the light transmittance of the microcrystalline glass. Especially for lithium aluminum silicon microcrystalline cover glass, the grain size and the transmittance in the wavelength range of 380-780nm are important indicators for judging the quality of the product. The light scattering of the grains and the light absorption of the transition metal ions are two key factors affecting the transparency of the material. Therefore, the introduction of metal oxide nucleating agents may greatly affect the optical properties of microcrystalline glass.
[0007] The requirements for mechanical strength of display cover glass are getting higher and higher. Not only does it need to further improve the surface hardness of the glass, but it also requires excellent scratch resistance and drop resistance. In addition to microcrystallization of the glass, surface chemical strengthening is usually required to improve the scratch resistance and drop resistance of the touch screen cover glass material, that is, by immersing the microcrystalline glass in alkali metal molten salt for ion exchange heat treatment to increase its surface compressive stress to achieve surface strengthening. In order to improve the ion exchange efficiency, it is necessary to optimize the glass composition through two ways. One is to increase the aluminum content in the alkali metal silicate glass so that Al enters the silicon oxygen network to increase the openness of the network and facilitate ion diffusion. The second is to increase the degree of connection of the glass network to increase the strain point temperature of the glass phase in the microcrystalline glass and minimize stress relaxation during the ion exchange process. Many process parameters of ion exchange chemical strengthening are strongly dependent on the composition of the original precursor glass. Since the addition of Al2O3 to the alkali silicate glass composition can improve the glass network structure, the dimension of the glass network increases, the network openness expands, and the transition temperature and strain point temperature of the glass increase nonlinearly. These factors are conducive to the ion exchange process.
[0008] Alkali-aluminosilicate glass has been shown to be a glass system more suitable for ion exchange than other glasses. The main reason is that this type of glass has a high concentration of mobile alkali metal ions and a more open network structure. In addition, the Al network strengthening makes the glass viscosity high enough and the strain point temperature high enough so that the compressive stress generated during the ion exchange process will not be relaxed, thereby improving the efficiency of ion exchange surface strengthening.
[0009] Therefore, it is necessary to design and develop a high-aluminum alkali-aluminosilicate glass composition suitable for microcrystallization and ion exchange strengthening without nucleating agents, as well as heat treatment process measures for preparing the glass composition into pure-phase transparent microcrystals. However, since high-aluminum glass is prone to devitrification and has a high melting temperature, the preparation of high-aluminum-silicon microcrystals that are easy to form and have high transparency is extremely sensitive to the composition. At present, there are still some problems in the preparation of microcrystals with excellent performance and Al2O3 mass percentage content higher than 20%, which requires the optimization of the precursor glass composition and crystallization heat treatment process to adapt to the influence of high aluminum content on the preparation and performance of microcrystals.
[0010] Therefore, a new solution to the above problems needs to be proposed. Summary of the invention
[0011] The purpose of the present invention is to provide a method for preparing lithium aluminum silicon microcrystalline glass with high aluminum content without a nucleating agent, and to prepare transparent microcrystalline glass with high light transmittance and excellent mechanical properties through a crystallization heat treatment process, so as to address the shortcomings of adding nucleating agents in the preparation of microcrystalline glass and the glass composition in the ion exchange surface strengthening of microcrystalline glass.
[0012] To achieve the above object, the present invention provides the following technical solution: a method for preparing lithium aluminum silicon glass-ceramics with high aluminum content without a nucleating agent, comprising the following steps:
[0013] S1: preparing precursor glass by melt cooling method, wherein the melt cooling method for preparing precursor glass comprises at least the following steps: designing the composition of precursor glass, preparing batch materials and melting glass;
[0014] S2: preparing lithium aluminum silicon glass-ceramics by crystallization heat treatment, wherein the preparing lithium aluminum silicon glass-ceramics by crystallization heat treatment adopts a two-step heat treatment method to prepare transparent glass-ceramics.
[0015] Preferably, the precursor glass in S1 comprises 6% to 9% by weight of Li2O; 14% to 30% by weight of Al2O3; 48% to 65% by weight of SiO2; 2% to 5% by weight of B2O3; 1% to 4% by weight of MgO; 1% to 6% by weight of ZnO; and 1 to 3% by weight of CaO.
[0016] Among them, SiO2 and B2O3 are glass network former oxides, and Al2O3 is a network intermediate, forming an aluminum-oxygen tetrahedron reinforced glass network structure;
[0017] Li2O, MgO, CaO and ZnO are network modifier oxides used to reduce the glass melting temperature and provide free oxygen to make alumina form aluminum-oxygen tetrahedron to supplement the glass network;
[0018] CaO also plays a role in reducing the high-temperature viscosity of the glass liquid;
[0019] MgO and ZnO also play a role in regulating the crystallization properties of glass;
[0020] The combined addition of Li2O, MgO and CaO can exert a mixed alkali effect to adjust the density and hardness of the glass.
[0021] Preferably, the role of ions in the network gap of Li2O, MgO, CaO, and ZnO in the glass composition includes two aspects: depolymerization and accumulation according to their ability to combine with oxygen;
[0022] The ability of interstitial cations to bind or release free oxygen can be measured by the electric field strength F:
[0023] F=Zc / (rc+rO)2
[0024] Where: Z c —cation valence number; r c —radius of the cation; r o —Radius of oxygen ions. When determining the glass composition, select network-modified oxides such as alkali metals, alkaline earth metals, and ZnO with higher F values, and keep the ratio of their total molar content to the total molar content of Al2O3 greater than 1.
[0025] Preferably, the batch preparation includes at least the following steps: introducing the oxides constituting the glass using inorganic non-metallic chemical raw materials or mineral powders with a particle size of 100 to 200 meshes, calculating the required raw materials according to the glass composition, accurately weighing the required raw materials to prepare the batch, and fully mixing the batch through a mixing device.
[0026] Preferably, the glass melting comprises at least the following steps: the mixed batch materials are melted at a maximum temperature of 1400-1550°C to form a clarified glass liquid, which is then cooled and formed into a precursor glass product with a geometric shape, and then annealed at 500-550°C to eliminate internal stress in the glass.
[0027] Preferably, the two-step heat treatment method for preparing transparent microcrystalline glass includes at least the following steps: slowly heating the precursor glass to the nucleation temperature at 2-5°C / min and keeping it warm for 1-3 hours, then slowly heating it to the crystallization temperature at 2-5°C / min and keeping it warm for 20-60 minutes, and then naturally cooling it in the furnace.
[0028] Preferably, the nucleation temperature and the crystallization temperature are determined by performing differential scanning calorimetry analysis on the glass.
[0029] Preferably, the glass transition temperature, crystallization onset temperature and crystallization peak temperature are obtained according to the differential scanning calorimetry analysis curve, the nucleation temperature is determined to be from the glass transition temperature to the crystallization onset temperature, and the crystallization temperature is the crystallization peak temperature.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The glass precursor composition of the present invention does not contain a nucleating agent, which is not only conducive to reducing the coloring of the glass and the decrease in light transmittance caused by the metal ions of the nucleating agent, but also a single crystal phase can be formed in the microcrystalline glass of the composition of the present invention, and the crystallization phase is close to the main composition of the glass phase, which reduces the refractive index difference between the crystallization phase and the glass phase, and improves the light transmittance of the microcrystalline glass. The high-aluminum glass composition of the present invention helps to improve the ion exchange surface strengthening efficiency of the microcrystalline glass. The lithium aluminum silicon microcrystalline glass can be prepared by using the composition and process of the present invention with common chemical raw materials and mineral powders containing Li2O, Al2O3, SiO2, MgO, ZnO, CaO, and B2O3, which has the advantages of reduced cost and simple and easy production process. The heat treatment temperature and time adjustment range of preparing microcrystalline glass by the two-step method are wide, and the grain size of transparent microcrystalline glass and the physical properties of microcrystalline glass can be conveniently regulated according to needs;
[0032] 2. The present invention can ensure that Al strengthens the silicon-oxygen network structure of the glass in a tetrahedral structure through the high aluminum content and the appropriate proportion of metal oxides in the glass composition, thereby improving the mechanical properties of the glass. At the same time, the glass phase has a more open network structure, which is beneficial to the subsequent ion exchange surface strengthening. In addition, the glass transition temperature of the prepared glass is higher than 510°C, and increases with the increase of Al2O3 content. The strain point temperature also increases accordingly, which is significantly higher than the melting point of alkali metal nitrates, which is beneficial to inhibiting stress relaxation in ion exchange and improving ion exchange efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0034] Figure 1 It is a schematic diagram of the overall process of the present invention;
[0035] Figure 2 This is the thermal analysis DSC curve of the glass in Example 2 of the present invention;
[0036] Figure 3 The X-ray diffraction pattern of the glass-ceramics of Example 2
[0037] Figure 4 This is a scanning electron microscope photograph of the glass-ceramics of Example 2 of the present invention after being etched with 10% hydrofluoric acid;
[0038] Figure 5 This is a graph of UV / visible light transmittance of the glass and glass-ceramics of Example 2 of the present invention;
[0039] Figure 6 is a differential scanning calorimetry analysis diagram of the glass in Example 3 of the present invention;
[0040] Figure 7 This is the XRD diffraction pattern of the glass-ceramics of Example 3 of the present invention;
[0041] Figure 8 This is a scanning electron microscope photograph of the glass-ceramics of Example 3 of the present invention after being etched with 10% hydrofluoric acid;
[0042] Fig. 9 This is a graph of the UV / visible light transmittance of the glass and microcrystalline glass according to Example 3 of the present invention. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0044] Embodiment 1:
[0045] A method for preparing lithium aluminum silicon glass-ceramics with high aluminum content without a nucleating agent comprises the following steps:
[0046] S1: preparing precursor glass by melt cooling method, which comprises at least the following steps: designing the composition of precursor glass, preparing batch materials and melting glass;
[0047] S2: Crystallization heat treatment to prepare lithium aluminum silicon glass-ceramics. Crystallization heat treatment to prepare lithium aluminum silicon glass-ceramics adopts a two-step heat treatment method to prepare transparent glass-ceramics.
[0048] 9. The precursor glass in S1 has a composition of 6% to 9% by weight of Li2O; 14% to 30% by weight of Al2O3; 48% to 65% by weight of SiO2; 2% to 5% by weight of B2O3; 1% to 4% by weight of MgO; 1% to 6% by weight of ZnO; and 1 to 3% by weight of CaO.
[0049] Among them, SiO2 and B2O3 are glass network former oxides, and Al2O3 is a network intermediate, forming an aluminum-oxygen tetrahedron reinforced glass network structure;
[0050] Li2O, MgO, CaO and ZnO are network modifier oxides used to reduce the glass melting temperature while maintaining the ratio of the total molar content of Li2O, MgO, CaO and ZnO to the total molar content of Al2O3 greater than 1, providing free oxygen to allow alumina to form aluminum-oxygen tetrahedrons to supplement the glass network;
[0051] CaO also plays a role in reducing the high-temperature viscosity of the glass liquid;
[0052] MgO and ZnO also play a role in regulating the crystallization properties of glass;
[0053] The combined addition of Li2O, MgO and CaO can exert a mixed alkali effect to adjust the density and hardness of the glass.
[0054] The role of ions in the network gaps of Li2O, MgO, CaO, and ZnO in the glass composition includes two aspects: depolymerization and accumulation according to their ability to combine with oxygen;
[0055] The ability of interstitial cations to bind or release free oxygen can be measured by the electric field strength F;
[0056] F=Zc / (rc+rO)2
[0057] Where: Z c —cation valence number; r c —radius of the cation; r o —Radius of oxygen ion.
[0058] These alkali metal and alkaline earth metal ions have high electric field strength and are prone to local accumulation in the structure, which increases the range of short-range order and increases the tendency of glass crystallization. + The ion radius is small and the electric field strength is large, which can significantly improve the chemical stability, surface tension and crystallization ability of the glass, and has strong migration ability in the glass matrix. 2+ Mg 2+ The displacement ability in the glass is very small and it is generally not easy to precipitate from the glass. These network modifier cations with high electric field strength in the precursor glass have a polarizing effect on the bridging oxygen of the adjacent silicon-oxygen tetrahedron, weakening the Si-O bond and causing the [Si(Al)O4] tetrahedral structural unit to depolymerize from the glass network. During the crystallization heat treatment process, they interact with the Li+ with strong migration ability. + Combined to form Li x Al x Si 1-x O2 crystal nuclei further grow into grains and precipitate from the glass matrix to form β-quartz derivative solid solution microcrystals.
[0059] The preparation of the batch material includes at least the following steps: introducing the oxides of the glass composition using inorganic non-metallic chemical raw materials or mineral powders with a particle size of 100-200 mesh, calculating the required raw materials according to the glass composition, accurately weighing the required raw materials to prepare the batch material, and fully mixing the batch material through a mixing device.
[0060] Glass melting includes at least the following steps: melting the mixed batch materials at a maximum temperature of 1400-1550°C into a clarified glass liquid, cooling and forming it into a precursor glass product with a geometric shape, and then annealing at 500-550°C to eliminate the internal stress of the glass.
[0061] The two-step heat treatment method for preparing transparent microcrystalline glass includes at least the following steps: slowly heating the precursor glass to the nucleation temperature at 2-5°C / min and keeping it warm for 1-3 hours, then slowly heating it to the crystallization temperature at 2-5°C / min and keeping it warm for 20-60 minutes, and then naturally cooling it in the furnace.
[0062] The nucleation temperature and crystallization temperature were determined by differential scanning calorimetry (DSC) analysis of the precursor glass.
[0063] The glass transition temperature (T) was obtained from the differential scanning calorimetry curve. g ), crystallization starting temperature (T x) and crystallization peak temperature (T p ), determine the nucleation temperature as T g ~T x The crystallization temperature is the peak crystallization temperature (T p )
[0064] The present invention provides a microcrystalline glass precursor formula with a specific composition, which can promote the nucleation and crystallization of the glass precursor into microcrystalline glass without the aid of a nucleating agent, and has good light transmittance. Sufficient Li2O, MgO, CaO and ZnO can reduce the melting temperature and insulation time during the glass melting process, thereby improving production efficiency. In the high-alumina silicate glass network, Al 3+ It can exist in two forms: forming aluminum oxide tetrahedron [AlO4] in a four-coordinated form and forming aluminum oxide octahedron [AlO6] in a six-coordinated form. Aluminum oxide tetrahedron [AlO4] participates in the glass network and connects with silicon oxide tetrahedron [SiO4] to repair the network, reducing network breaks and non-bridging oxygen. As the Al2O3 content in the sample increases, more [AlO6] is converted into [AlO4] to participate in network construction, reducing the number of non-bridging oxygen, increasing the degree of glass network connectivity, and at the same time, the metal ions of the network modifier fill the network gaps, making the glass structure denser. Glass microcrystallization allows the glass matrix to be embedded with nano-scale quartz solid solution grains with a harder hardness that are similar to the main glass composition, forming an inorganic composite material and improving the surface hardness and scratch and drop resistance of microcrystalline glass. Due to the Li in microcrystalline glass x Al x Si 1-x O2 or Li2Al2Si3O 10 The grains have a similar composition to the main glass, and their refractive index is close to that of the glass matrix, which is conducive to maintaining a high light transmittance.
[0065] Example 2:
[0066] In view of the above-mentioned embodiment 1, a Li-containing x Al x Si 1-x Preparation of glass-ceramics of O2 crystals;
[0067] Step 1: Prepare the raw materials. According to the composition of glass (mass percentage):
[0068] 7.94% Li2O-20.33% Al2O3-59.89% SiO2-2.68% MgO-4.06% ZnO%-2.79% CaO-2.31% B2O3, calculate and weigh the batch materials. The oxides in the composition are introduced by analytically pure lithium carbonate, aluminum hydroxide, quartz sand, basic magnesium carbonate pentahydrate, zinc oxide, calcium carbonate, and boron oxide powder. Put the mixture into a ball mill and grind it thoroughly on a ball mill for 1 hour.
[0069] Step 2: Precursor glass melting and molding. The mixture is placed in an alumina crucible and heated to 1500°C in a high-temperature electric furnace at a rate of 10°C / min and kept at that temperature for 3 hours to fully melt the raw material powder into a clear glass liquid for casting.
[0070] Step 3: Annealing of precursor glass. The formed glass is immediately placed in an annealing furnace preheated to 500°C for 1 hour and then cooled naturally in the furnace to eliminate residual thermal stress in the glass.
[0071] Step 4: Preparation of lithium aluminum silicon glass-ceramics
[0072] The thermal analysis DSC curve of the glass in Example 2 is as follows: Figure 2 As shown, according to the DSC curve, the glass transition temperature T g The temperature of the precursor glass is 548°C, the crystallization start temperature is 633°C, and the first crystallization peak temperature is 663°C. The nucleation temperature of the precursor glass heat treatment is determined to be 20-40°C above the glass transition temperature, and the crystallization temperature is the temperature of the first crystallization peak. The precursor glass obtained in step 3 is first heated to 535°C at 5°C / min and then kept warm for 2h for nucleation treatment, and then continued to heat to 663°C and kept warm for 0.5h for crystallization treatment. After cooling in the furnace, transparent lithium aluminum silicon microcrystalline glass is obtained.
[0073] Figure 3 This is the X-ray diffraction spectrum of the glass-ceramics of Example 2. The main crystal phase of the diffraction peak in the figure is Li x Al x Si 1-x O2 solid solution (PDF#40-0073). Figure 4 This is a scanning electron microscope photograph of the sample of Example 2 after the surface glass phase was corroded by 10% hydrofluoric acid. The clusters are converted into nanocrystals and are evenly distributed in the glass matrix. Figure 5 This is the transmittance curve of Example 2. The transmittance of glass and glass-ceramics is about 90%.
[0074] Embodiment three:
[0075] In view of the above-mentioned embodiment 1, a Li2Al2Si3O 10 Preparation of crystalline glass-ceramics;
[0076] Step 1: Prepare the raw materials. Weigh the raw materials by mass percentage (wt%): 7.62% Li2O-29.26% Al2O3-49.81% SiO2-3.21% MgO-5.19% ZnO-2.68% CaO-2.22% B2O3. Calculate and weigh the batch materials. The oxides in the composition are introduced by analytically pure lithium carbonate, aluminum hydroxide, quartz sand, basic magnesium carbonate pentahydrate, zinc oxide powder, calcium carbonate, and boron oxide powder. Put the mixture into a ball mill and grind it thoroughly on a ball mill for 1 hour.
[0077] Step 2: Precursor glass melting and molding. The mixture is placed in an alumina crucible and heated to 1500°C in a high-temperature electric furnace at a rate of 10°C / min and kept at that temperature for 3 hours to fully melt the raw material powder into a clear glass liquid for casting.
[0078] Step 3: Immediately place the formed glass in an annealing furnace preheated to 550°C and keep it warm for 1 hour, then cool it naturally in the furnace to eliminate the residual internal stress in the glass.
[0079] Step 4: Preparation of lithium aluminum silicon glass-ceramics by heat treatment
[0080] The thermal analysis DSC curve of the glass in Example 3 is as follows: Figure 6 As shown, according to the DSC curve, the glass transition temperature T g The crystallization temperature is 610℃, the crystallization start temperature is 690℃, and the first crystallization peak temperature is 724℃. g The temperature increases significantly, and the corresponding strain point temperature also increases. According to the glass crystallization and nucleation temperature shown by the DSC curve, the precursor glass obtained in step 3 is first heated to 643°C and then kept warm for 2 hours for nucleation treatment, and then further heated to 724°C and kept warm for 0.5 hours for crystallization treatment, and then cooled in the furnace to obtain transparent lithium aluminum silicon microcrystalline glass.
[0081] Figure 7 This is the XRD spectrum of the glass-ceramics of Example 3. The main crystal phase of the diffraction peak in the figure is spodumene (Li2Al2Si3O 10 ) crystals (PDF#25-1183). Figure 8 This is a scanning electron microscope photograph of the glass-ceramics of Example 3 after being etched with 10% hydrofluoric acid, in which the nanocrystals are uniformly distributed in the glass matrix. Fig. 9 The UV-visible light transmittance of the glass and glass-ceramics in the range of 200-1000 nm of the sample of Example 3 is above 90% for the original precursor glass and above 85% for the glass-ceramics. The transmittance can be further increased to above 90% after grinding and polishing.
[0082] With respect to the above-mentioned embodiments, the examples described in the present invention are laboratory preparation schemes. The composition and glass and glass-ceramic preparation process conditions described in the present invention are also applicable to similar industrial production processes and have the following characteristics:
[0083] Composition of nucleating agent-free lithium aluminum silicon glass-ceramics. The specific mass percentage of the lithium aluminum silicon glass-ceramics is 6% to 9% Li2O; 14% to 30% Al2O3; 48% to 65% SiO2; 2% to 5% B2O3; 1% to 4% MgO; 1% to 6% ZnO; 1 to 3wt% CaO. Among them, SiO2 and B2O3 are glass network former oxides, and Al2O3 is a network intermediate, which strengthens the glass network structure by forming aluminum oxide tetrahedrons. Li2O, MgO, CaO and ZnO are network modifier oxides, which play two roles of depolymerization and aggregation. On the one hand, the glass network is depolymerized to reduce the glass melting temperature, and its content ensures that free oxygen can be provided to make aluminum oxide form aluminum oxide tetrahedrons to supplement the glass network; on the other hand, the aggregation effect promotes the precipitation of silicate crystals during the crystallization heat treatment process. In addition, CaO also plays a role in reducing the high temperature viscosity of glass liquid, and MgO and ZnO also play a role in adjusting the crystallization performance of glass. The combined addition of Li2O, MgO, and CaO can exert the mixed alkali effect to adjust the density and hardness of glass.
[0084] (2) The glass contains up to 30% Al2O3 by mass percentage. In lithium aluminosilicate glass, as the Al content increases, aluminum preferentially enters the glass Si-O network in the form of tetrahedral [AlO4] to avoid forming an [AlO6] octahedral structure with Al-O-Al bonds, i.e. [AlO 6 / 2 ]+[O]→[AlO4], the adjacent metal ions in the network gap maintain the electrical neutrality of the [AlO4] structure, and the coordination number of Al increases with the increase of the electric field strength of the metal ions in the network gap. Therefore, there will be a small amount of penta-coordinated [AlO5] and hexa-coordinated [AlO6] aluminum oxygen structural units in the glass. Adding a higher content of alumina to silicate glass will increase the degree of polymerization of the glass network due to Al entering the network as a network former. When there are enough alkali metal oxides in the composition to provide free oxygen, the degree of polymerization of the glass network increases with the increase of the Al / Si ratio. The higher the electric field strength of the metal ions outside the network, the higher the oxygen coordination number of aluminum, and the higher the content of penta-coordinated [AlO5] and hexa-coordinated [AlO6] in the glass matrix.
[0085] (3) By utilizing the high electric field strength of Li2O, CaO, MgO and ZnO, the metal ions produce a greater accumulation effect and provide more non-bridging oxygen, which promotes crystallization in the absence of a nucleating agent, and the crystallization heat treatment temperature and time adjustment range for preparing highly transparent microcrystalline glass is wider. In silicate glass, the degree of network connection has an important influence on the crystallization of the glass. Generally speaking, the tighter the network connection, the less likely it is to adjust to a regular arrangement during the heat treatment process, that is, the less likely it is to crystallize. Therefore, as the Al2O3 content in the glass composition increases, Al enters the network structure in the form of tetrahedrons and continuously strengthens the glass silicon oxygen network, which will significantly reduce the crystallization ability and accumulation degree of the glass. In order to promote the conversion of the precursor glass into microcrystalline glass through crystallization heat treatment, the present invention selects metal oxides Li2O, CaO, MgO and ZnO with a greater electric field strength as glass network modifiers, which produce a greater accumulation effect and provide more non-bridging oxygen, increase the oxygen coordination number of Al, and appropriately increase the degree of network breakage, thereby promoting crystallization. This can promote the precipitation of β-quartz solid solution and also promote the transformation of β-quartz crystal phase to β-spodumene phase.
[0086] (4) A two-step process is used to perform crystallization heat treatment on the precursor glass to prepare a transparent microcrystalline glass containing a nanocrystalline phase. The temperature is kept between the glass transition temperature and the crystallization start temperature for 1 to 3 hours for nucleation, and then the temperature is slowly increased at 2 to 5°C / min to the crystallization peak temperature and kept for 20 to 60 minutes for crystallization treatment.
[0087] (5) A lithium aluminum silicon glass-ceramic contains a single crystal phase with a composition close to that of a glass matrix, the grain size of which is nanometer-level and has a refractive index close to that of the glass matrix, and the light transmittance of the glass-ceramic is higher than 90%. The glass matrix in the glass-ceramic has a more open network structure, and the glass-ceramic using this system is suitable for surface chemical strengthening using an ion exchange process.
[0088] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing lithium aluminum silicon glass-ceramics with high aluminum content without a nucleating agent, characterized in that: The following steps are involved: S1: preparing precursor glass by melt cooling method, wherein the melt cooling method for preparing precursor glass comprises at least the following steps: designing the composition of precursor glass, preparing batch materials and melting glass; The precursor glass in S1 has a composition of 7.62% to 9% Li2O by mass percentage; 14% to 30% Al2O3; 48% to 65% SiO2; 2% to 5% B2O3; 1% to 4% MgO; 1% to 6% ZnO; 1 to 3wt% CaO, the total mass percentage of the above components is 100%; The ratio of the total molar content of Li2O, MgO, CaO and ZnO to the molar content of Al2O3 is greater than 1; S2: preparing lithium aluminum silicon glass-ceramics by crystallization heat treatment, wherein the preparing lithium aluminum silicon glass-ceramics by crystallization heat treatment adopts a two-step heat treatment method to prepare transparent glass-ceramics; The crystal phase of the transparent microcrystalline glass is Li2Al2Si3O 10 ; The two-step heat treatment method for preparing transparent microcrystalline glass comprises at least the following steps: The precursor glass is slowly heated to the nucleation temperature at 2-5°C / min and kept at this temperature for 1-3 hours, and then slowly heated to the crystallization temperature at 2-5°C / min and kept at this temperature for 20-60 minutes, and then cooled naturally along with the furnace; The nucleation temperature and crystallization temperature are determined by differential scanning calorimetry analysis of the glass; The glass transition temperature, crystallization onset temperature and crystallization peak temperature were obtained according to the differential scanning calorimetry analysis curve. The nucleation temperature was determined to be the temperature from the glass transition temperature to the crystallization onset temperature, and the crystallization temperature was the crystallization peak temperature.
2. The method for preparing a nucleating agent-free lithium aluminum silicon glass-ceramics with high aluminum content according to claim 1, characterized in that: The batch material preparation comprises at least the following steps: The oxides constituting the glass are introduced by inorganic non-metallic chemical raw materials or mineral powders with a particle size of 100 to 200 meshes, the required raw materials are calculated according to the glass composition, and the required raw materials are accurately weighed to prepare a batch material, and the batch material is fully mixed by a mixing device.
3. The method for preparing a nucleating agent-free lithium aluminum silicon glass-ceramics with high aluminum content according to claim 2, characterized in that: The glass melting comprises at least the following steps: the mixed batch materials are melted at 1400-1550°C to form a clear glass liquid, which is then cooled and formed into a precursor glass product with a geometric shape, and then annealed at 500-550°C to eliminate the internal stress of the glass.
Citation Information
Patent Citations
Chemically strengthenable self-crystallizing glass ceramic and preparation method thereof
CN110104955A